Electroplated component and method for manufacturing same

By forming a hard layer containing chromium, carbon, and oxygen on the chromium electroplating film of the 3V chromium bath, and improving the crystallization degree through heating treatment, the problem of easy destruction of the electroplating film during grinding is solved, and the effect of high hardness and wear resistance is achieved.

CN119816628APending Publication Date: 2025-04-11ASTEMO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063626.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-07
Filing Date
2023-09-05
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When grinding a sliding member of the chromium electroplating film with a 3-valent chromium bath, a problem of brittle damage (leaving damage) of the electroplating film is prone to occur.

Method used

By forming a hard layer containing chromium, carbon and oxygen on the outer surface of the electroplating film, the chromium content of the electroplating film reaches more than 60 at% and the carbon content is between 1 at% and 30 at%, and the crystallinity degree reaches more than 5% by heating treatment to improve the hardness and wear resistance of the electroplating film.

Benefits of technology

It is achieved that the peeling failure is difficult to produce during the grinding process, while maintaining the environmental advantages compared with 6-valent chromium, and avoiding brittle damage of the electroplating film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816628A_ABST
    Figure CN119816628A_ABST
Patent Text Reader

Abstract

A plated member having, on the outer surface thereof, a plated coating that contains at least chromium, carbon, and oxygen and contains, as the main component, chromium used in a trivalent chromium bath, the plated coating containing 60 at% or more of chromium and 1 at%-30 at% of carbon, the press-in hardness of the outer surface being 11.1 GPa or more, and the peak integrated intensity ratio of the measured value as measured by X-ray diffraction and the degree of crystallization as calculated by formula (1) being 5% or more, degree of crystallization (peak integrated intensity ratio) = {(crystallinity) / (crystallinity + amorphous)} * 100% (1) where the indentation hardness is a value measured by instrumented indentation hardness by nanoindentation (ISO 14577), and the integrated intensity ratio of the formula (1) is a value determined at 2 [theta]: 30 DEG to 60 DEG, the half-value width of crystallinity: < 3, and the half-value width of amorphous: > = 3 in XRD (X-ray diffraction) analysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electroplated parts and methods of making the same.

[0002] This application claims priority based on Japanese Patent Application No. 2022-142217 filed in Japan on September 7, 2022, the contents of which are cited herein. Background Art

[0003] Patent Document 1 listed below describes a technique for using a chromium electroplating layer of trivalent chromium, which has no problem in terms of toxicity and pollution generation compared with hexavalent chromium, for a plate-making roller.

[0004] Prior Art Literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-143169 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] Among chromium plating films formed on rods that come into sliding contact with sliding parts, chromium plating films using a trivalent chromium bath have attracted attention as an alternative to hexavalent chromium plating films.

[0009] However, according to the research conducted by the present inventors, when a rod having a chromium plating film formed thereon using a conventional trivalent chromium bath is polished, brittle failure (peeling failure) of the plating film occurs.

[0010] An object of the present invention is to provide a plated component such as a rod having a chromium electroplated film using a trivalent chromium bath that is less likely to be delaminated during polishing, and a method for producing the same.

[0011] Means for solving problems

[0012] A plated component according to one embodiment of the present invention has, on its outer surface, a plated film containing at least chromium, carbon, and oxygen and having chromium as a main component using a trivalent chromium bath,

[0013] The electroplated film contains chromium: 60 at% or more, carbon: 1 at% to 30 at%, and the indentation hardness of the outer surface is 11.1 GPa or more.

[0014] The peak integrated intensity ratio of the measured value of the X-ray diffraction measurement and the crystallinity calculated by the following formula (1) is 5% or more,

[0015] Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1)

[0016] The indentation hardness is a value obtained by measuring the instrumented indentation hardness using the nanoindentation method (ISO 14577). The integrated intensity ratio of formula (1) is a value obtained by XRD (X-ray diffraction) analysis using 2θ of 30° to 60°, a half-value width of crystalline material of <3, and a half-value width of amorphous material of ≥3.

[0017] In addition, a method for manufacturing an electroplated component according to one embodiment of the present invention is a method for manufacturing an electroplated component, wherein the electroplated component has an electroplated film on its outer surface that includes at least chromium, carbon, and oxygen and has chromium as its main component using a trivalent chromium bath, the electroplated film contains chromium: 60at% or more, carbon: 1at%~30at%, and the indentation hardness of the outer surface is 11.1GPa or more. In the electroplated film, the peak integrated intensity ratio of the measured values ​​measured by X-ray diffraction measurement and the degree of crystallization calculated according to the following formula (1) are 5% or more. The method for manufacturing the electroplated component has an electroplating step of forming an electroplated film composed of a hard layer with chromium as its main component on the surface of the electroplated component, the electroplating step having a first step of forming an amorphous electroplated film; and a second step of heating and crystallizing the amorphous electroplated film formed in the first step.

[0018] Effects of the Invention

[0019] According to the above-mentioned aspect of the present invention, it is possible to provide a plated component having a chromium plated coating mainly composed of chromium using a trivalent chromium bath which is less environmentally friendly than hexavalent chromium and which is less susceptible to peeling damage during polishing. In addition, it is possible to provide a manufacturing method for manufacturing the plated component. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a diagram showing the overall structure of a shock absorber including a piston rod as a first embodiment of a plated component according to the present invention, and is a cross-sectional view taken along a cross section including a center line CL.

[0021] Figure 2 It is a side view showing a rough shape of the piston rod.

[0022] Figure 3 is a diagram showing the upper structure of the shock absorber. Figure 1 An enlarged partial cross-sectional view of section A.

[0023] Figure 4 is a diagram showing the structure of the front end portion of the piston rod. Figure 1 An enlarged partial cross-sectional view of part B.

[0024] Figure 5 This is a flow chart showing an example of the manufacturing process of the piston rod.

[0025] Figure 6This is a perspective view of the main parts showing an example of a grinding device used for grinding the outer diameter of the piston rod.

[0026] Figure 7 This is a graph showing the relationship between the film formation rate and the degree of crystallinity of the plated films formed in Examples.

[0027] Figure 8 This is a graph showing the relationship between the film formation rate and the impurity element concentration of the plated films formed in Examples.

[0028] Fig. 9 This is a table showing the physical property values ​​of the plated films formed in Examples.

[0029] Fig.10 This is a table showing the relationship between the physical property values ​​of the plated films formed in Examples and the heat treatment temperature.

[0030] Fig.11 The figures show polishing marks of a brittle mode of a plating film formed on a sample of a comparative example. (A) is a photograph enlarged at 500 times magnification, and (B) is a photograph enlarged at 5000 times magnification.

[0031] Fig.12 The polishing marks show the ductility mode of the plated film formed on the sample of the example. (A) is a photograph enlarged by 500 times, and (B) is a photograph enlarged by 5000 times.

[0032] Fig.13 (A) is a diagram showing the analysis results of X-ray diffraction of a comparative example sample, and (B) is a surface photograph showing polishing marks of the sample.

[0033] Fig.14 (A) is a diagram showing the results of X-ray diffraction analysis of an example sample heat-treated at 250° C., and (B) is a surface photograph showing polishing marks of the sample.

[0034] Fig.15 (A) is a diagram showing the results of X-ray diffraction analysis of an example sample heat-treated at 300° C., and (B) is a surface photograph showing polishing marks of the sample.

[0035] Fig.16 This is a graph showing the relationship between the heat treatment temperature (baking temperature) and the maximum polishing scratch width in the example samples and the comparative example samples.

[0036] Fig.17 This is a graph showing the relationship between the heat treatment temperature (baking temperature) and the number of polishing marks having a width of 8 μm or more in the samples of the examples and the samples of the comparative examples.

[0037] Fig.18This is a graph showing the relationship between the heat treatment temperature (baking temperature) and the coating hardness in the samples of the examples and the samples of the comparative examples.

[0038] Fig.19 This is a graph showing the relationship between the heat treatment temperature (baking temperature) and the degree of crystallization in the samples of the examples and the samples of the comparative examples.

[0039] Fig. 20 This is a graph showing the relationship between the coating hardness and the number of polishing marks having a width of 8 μm or more in the samples of the examples and the samples of the comparative examples.

[0040] Fig.21 This is a graph showing the relationship between the degree of crystallization and the number of polishing marks having a width of 8 μm or more in the samples of the examples and the samples of the comparative examples.

[0041] Fig. 22 This is a graph showing the relationship between the film hardness and the degree of crystallinity of the samples of the examples and the samples of the comparative examples. DETAILED DESCRIPTION

[0042] Hereinafter, a shock absorber (cylinder device) including a piston rod as one embodiment of the plated component of the present invention will be described.

[0043] It should be noted that the embodiments described below are specifically described for better understanding of the gist of the invention, and do not limit the present invention unless otherwise specified. In addition, the drawings used in the description of the embodiments shown below are appropriately scaled to make it easier to see each part.

[0044] Figure 1 It is a partial cross-sectional view showing the overall structure of a shock absorber (cylinder device) 1 including a piston rod 21 as an example of a plated component of the present invention.

[0045] A plating film described later is formed on the outer peripheral surface of the piston rod 21 . Before describing the plating film, the overall structure of the shock absorber 1 will be described.

[0046] "Cylinder device"

[0047] Figure 1 The cylinder device 1 shown is a shock absorber for a suspension device of an automobile or a railway vehicle, and more specifically, a strut-type suspension device of an automobile. The cylinder device 1 comprises: a cylindrical inner cylinder (cylinder) 2 in which a working fluid is sealed, and an outer cylinder 3 having a larger diameter than the inner cylinder 2 and disposed on the outer circumference of the inner cylinder 2, with a bottomed cylindrical outer cylinder 3 in which a working fluid and a working gas are sealed to form a storage chamber R between the inner cylinder 2. The cylinder device 1 is a double-cylinder shock absorber in which the inner cylinder 2 is disposed in the outer cylinder 3. Figure 1 CL in the figure represents the center line of the inner tube 2 and the outer tube 3 .

[0048] The outer tube 3 has a cylindrical side wall portion 7 and a bottom 8 that blocks one axial end side of the side wall portion 7. The inner tube 2 is cylindrical. The inner tube 2 is engaged with the bottom 8 of the outer tube 3 via an annular base valve 13 installed at one axial end thereof. The inner tube 2 is engaged with the other axial end side of the side wall portion 7 via an annular rod guide portion 11 installed at the other axial end thereof.

[0049] The base valve 13 is disposed coaxially with the outer tube 3 , and the stem guide 11 is fitted with the inner tube 2 and the outer tube 3 to support the other end of the inner tube 2 coaxially with the outer tube 3 .

[0050] An oil seal 15 is disposed on the rod guide portion 11 on the side opposite to the bottom portion 8. A locking portion 16 bent inward is formed on the other axial end of the side wall portion 7, and the oil seal 15 is supported by the locking portion 16.

[0051] A piston 25 is slidably fitted in the inner tube 2. The piston 25 divides the inner tube 2 into a first chamber 22 and a second chamber 23. The first chamber 22 is formed between the piston 25 and the rod guide 11, and the second chamber 23 is formed between the piston 25 and the base valve 13. The second chamber 23 is divided from the storage chamber R by the base valve 13 provided on one end side of the inner tube 2.

[0052] The metal piston rod 21 is connected to the piston 25 by a nut 26. The piston rod 21 has a cylindrical large diameter portion 21a, and protrudes to the outside from one end side of the inner tube 2 and the outer tube 3 through the rod guide 11 and the oil seal 15. The large diameter portion 21a of the piston rod 21 is inserted slidably relative to the inner side of the rod guide 11 and the inner side of the oil seal 15. Thus, the oil seal 15 becomes a sliding member relative to the piston rod 21.

[0053] A small diameter portion 21 b is formed at the front end side of the piston rod 21 , and the piston 25 is inserted through the small diameter portion 21 b . The piston 25 is attached to the piston rod 21 by screwing a nut 26 into a threaded portion at the front end of the small diameter portion.

[0054] An annular groove 21c is formed in the large diameter portion 21a of the piston rod 21 near the small diameter portion 21b, and an annular inner stopper 24 is mounted to engage with the annular groove 21c. An annular rebound rubber 19 is disposed on the inner stopper 24.

[0055] like Figure 2 As shown, in the large diameter portion 21a of the piston rod 21, a portion between a position P1 separated from the annular groove 21c and a connection portion P2 connected to a bolt portion 21d as a mounting portion to the vehicle body constitutes a sliding range A.

[0056] An electroplated film mainly composed of chromium using a trivalent chromium bath described in detail later is formed on the outer peripheral surface of the piston rod 21 including the sliding range A.

[0057] The piston rod 21 moves axially together with the piston 25. The oil seal 15 through which the large diameter portion 21a of the piston rod 21 is inserted seals the inner tube 2 and the outer tube 3 with the piston rod 21 to prevent the working fluid in the inner tube 2, the working gas in the storage chamber R, and the working fluid from leaking to the outside.

[0058] like Figure 4 As shown, passages 27 and 28 penetrating in the axial direction are formed in the piston 25 . Figure 1 The passages 27 and 28 shown can communicate with the first chamber 22 and the second chamber 23. The piston 25 is provided with an annular disk valve 28a that can block the passage 28 by abutting against the upper surface of the piston 25. The piston 25 is provided with an annular disk valve 27a that can block the passage 27 by abutting against the lower surface of the piston 25.

[0059] The piston rod 21 moves to the shortening side ( Figure 1 When the piston 25 moves in the direction of narrowing the second chamber 23, the piston 25 moves in the direction of narrowing the second chamber 23. When the pressure of the second chamber 23 becomes higher than the pressure of the first chamber 22 by a predetermined value or more, the disk valve 28a opens the passage 28, and at this time, a damping force is generated.

[0060] The piston rod 21 moves to the extension side where the amount of protrusion from the inner tube 2 and the outer tube 3 increases toward the upper end side ( Figure 1 When the pressure in the first chamber 22 rises, the piston 25 moves in the direction of shortening the first chamber 22. As a result, when the pressure in the first chamber 22 is higher than the pressure in the second chamber 23 by a predetermined value or more, the disk valve 27a opens the passage 27, and a damping force is generated at this time.

[0061] like Figure 1 As shown, passages 29, 29 penetrating the base valve 13 in the axial direction are formed in the base valve 13. The passage 29 can communicate with the second chamber 23 and the storage chamber R. An annular disk valve 30 is arranged on the bottom surface side of the base valve 13 so as to block one passage 29 by abutting against the bottom surface side of the base valve 13. An annular disk valve 31 is arranged on the upper surface side of the base valve 13 so as to block the other passage 29 by abutting against the upper surface side of the base valve 13.

[0062] The disk valve 30 is a check valve that allows the working fluid to flow from the second chamber 23 to the reservoir chamber R through the passage 29 on one side, and restricts the working fluid from flowing in the opposite direction through the passage 29. The disk valve 30 is a valve that opens the passage 29 when the piston rod 21 moves toward the shortening side and the pressure in the second chamber 23 becomes higher than the pressure in the reservoir chamber R by a predetermined value or more.

[0063] The disk valve 31 is a check valve that allows the working fluid to flow from the reservoir chamber R to the second chamber 23 through the other passage 29, and restricts the working fluid from flowing in the opposite direction through the passage 29. The disk valve 31 is a valve that opens the passage 29 when the piston rod 21 moves to the extension side and the pressure of the second chamber 23 becomes lower than the pressure of the reservoir chamber R by a predetermined value or more.

[0064] like Figure 1 As shown, a mounting lug 33 is mounted on the outer side of the bottom portion 8. The cylinder device 1 is used by mounting the outer side portion of the piston rod 21 and the mounting lug 33 between relatively moving members as mounting objects.

[0065] The cylinder device 1 is used by, for example, connecting the outer end of the piston rod 21 to the body side of a vehicle and connecting the mounting eye 33 to the wheel side of the vehicle.

[0066] In the cylinder device 1, the piston rod 21 and the piston 25 are integrally slid in the inner tube 2 to change the volume of the first chamber 22 and the second chamber 23. At this time, the flow resistance of the liquid acting on the piston 25 and the base valve 13 can generate a damping force.

[0067] like Figure 3 As shown, the rod guide 11 is substantially stepped annular, with a large diameter portion 11a formed on one axial side and a small diameter portion formed on the other side. The large diameter portion 11a fits with the inner circumference of the outer tube 3, and the small diameter portion fits with the inner circumference of the inner tube 2.

[0068] An annular protrusion 11c protruding in the axial direction is formed at the end of the large diameter portion 11a of the rod guide 11, and a connecting hole 11d is formed corresponding to a portion of the annular protrusion 11c so as to allow the rod guide 11 to pass through in the axial direction. In the connecting hole 11d, the side of the rod guide 11 opposite to the annular protrusion side in the axial direction is open to the storage chamber R.

[0069] The oil seal 15 includes a sealing member body 37 which is an integrally formed product in which a metal annular member 36 is embedded in a sealing member 35 made of synthetic rubber, and a metal annular spring 38. The annular member 36 maintains the shape of the sealing member 35 and gives the sealing member body 37 a strength for fixing to a target part. The sealing member body 37 is mounted on the end side of the outer tube 3 by sandwiching the annular member 36 between the locking portion 16 and the annular convex portion 11c.

[0070] The sealing member 35 includes a dustproof lip portion 35 a , an oil seal lip portion 35 b , a seal ring portion 35 c , and a check lip portion 35 d , and surrounds the periphery of the piston rod 21 to perform a sealing function.

[0071] The cylinder device 1 is configured such that the piston rod 21 or the outer cylinder 3 is repeatedly subjected to external impact force along its axial direction when the vehicle is traveling. Whenever the impact force is applied, the piston rod 21 moves toward the shortening side or the extending side, and a damping force acts at this time. In this way, the cylinder device 1 functions as a buffer for the strut suspension of the automobile.

[0072] In addition, the outer peripheral surface of the piston rod 21 is provided with a plating film composed of chromium using a trivalent chromium bath described below. This plating film is a plating film that is unlikely to cause brittle failure (peeling failure) when the outer peripheral surface of the piston rod 21 is polished to the target surface roughness by outer diameter grinding during the manufacture of the piston rod 21. When the outer peripheral surface is finished to the polished surface with the target surface roughness and the piston rod 21 is provided with the plating film described in detail later, even if the large diameter portion 21a of the piston rod 21 repeatedly slides relative to the sealing member 35, excellent sliding characteristics can be generated, thereby obtaining excellent wear resistance.

[0073] Figure 5 This is a flowchart showing an example of a manufacturing process of the piston rod 21 .

[0074] like Figure 5 As shown in step S1 , in order to form the piston rod 21 , a rod material such as a steel bar made of a desired type of steel material is prepared.

[0075] The rod material is subjected to heat treatment such as high-frequency quenching and tempering in step S2 to be subjected to surface hardening treatment suitable for a piston rod.

[0076] Next, if Figures 1 to 4 As shown in the schematic form, cutting is performed in step S3, and outer diameter grinding is performed in step S4.

[0077] Next, Figures 1 to 4 The piston rod of the general form shown in the figure is subjected to a base electroplating treatment such as nickel electroplating in step S5, and then subjected to a chromium electroplating treatment mainly composed of chromium using a trivalent chromium bath in step S6. It should be noted that in step S5 of performing the base electroplating treatment, other base electroplating treatments may be performed instead of nickel electroplating, or the base electroplating may be omitted by omitting step S5 of performing the electroplating treatment.

[0078] After the electroplating treatment is performed in step S6, a heat treatment is performed in step S7. The heat treatment can be performed at 250°C to 400°C for several hours. It should be noted that after the electroplating treatment, a baking treatment can be performed for the purpose of removing hydrogen, or the baking treatment and the heat treatment can be used together.

[0079] Next, in step S7 , the outer diameter of the piston rod is ground, and the piston rod having the final surface shape can be obtained by precision finishing.

[0080] The present embodiment is characterized in that the plating treatment performed in step S6 and the heat treatment performed in step S7 form a chromium plating film mainly composed of chromium using a trivalent chromium bath on the piston rod.

[0081] The chromium electroplating film deposited in the trivalent chromium bath used in the present embodiment contains chromium as a main component and contains one or more impurity elements selected from carbon (C) and oxygen (O) as other elements.

[0082] For example, the chromium plating film preferably contains 60 at % or more of chromium and 1 at % to 30 at % of carbon, and has a surface indentation hardness of 11.1 GPa or more.

[0083] The indentation hardness refers to a value measured by instrumented indentation hardness using a nanoindentation method (ISO 14577). For example, an indentation weight of 20 mN may be used.

[0084] The chromium electroplated film may contain oxygen in an amount of about 2 to 6 at% among the above elements. Furthermore, in addition to the above elements, the chromium electroplated film may contain either chlorine (Cl) or iron (Fe) in an amount of about 5 at% or less as an impurity element.

[0085] In addition, the carbon content is more preferably about 8 at% to 25 at%, and the oxygen content is more preferably about 2 at% to 5 at%.

[0086] The chromium of the trivalent chromium bath constituting the electroplating film is used as the main component, and it is desired to contain as much as possible. As described later, the carbon contained in the electroplating film, considering the origin of the organic components constituting the electroplating bath, when the carbon content is less than 8at%, the possibility of peeling marks in the brittle mode during outer diameter grinding increases. According to the upper limit of the concentration of the organic salt added to the electroplating bath, the maximum carbon content that the electroplating film can contain is 30at%.

[0087] The oxygen content of the electroplated film is in the range of 2at% to 6at%.

[0088] When the oxygen content is less than 2 at %, there is a problem that the possibility of generating peeling marks in the brittle mode increases. When the oxygen content exceeds 6 at %, there is a problem that the possibility of generating peeling marks in the brittle mode increases as described above.

[0089] In the electroplated film of the present embodiment, elemental analysis can be performed by an electron probe micro analyzer (EPMA), and for example, conditions such as an acceleration voltage of 10 kV and an irradiation current of 100 nA can be employed.

[0090] It should be noted that in the specification of the present application, when a numerical range is specified, when the upper limit and the lower limit are indicated by "~", unless otherwise specified, the concept of including the upper limit and the lower limit is included. Therefore, the 1at% to 30at% indicates a range of 1at% to 30at%.

[0091] The impurity elements other than chromium are presumably derived from organic components such as carboxylate, pH buffer, and conductivity salt described below contained in the electroplating bath.

[0092] In the chromium electroplated film of the present embodiment, the content of impurities contained in the electroplated film varies depending on the electroplating treatment conditions, and is related to the current density, bath temperature, and pH conditions.

[0093] This is presumably because the availability of additives during chromium precipitation is affected by current density (reduction rate), bath temperature (reduction rate), and pH (complex formation, reduction rate).

[0094] In the present embodiment, the plating bath used for the chromium plating treatment may contain a trivalent chromium salt and various components such as a complexing agent, a pH buffer, and a conductivity salt as additives.

[0095] As the trivalent chromium salt, chromium chloride, chromium sulfate, basic chromium sulfate, etc. can be used, and among these, chromium chloride is preferably used.

[0096] As the complexing agent, glycine, formic acid, oxalic acid, acetic acid, and the like, which are carboxylates, can be used. Among these, glycine is preferably used.

[0097] As the pH buffer, boric acid, citric acid, and the like can be used, and among these, boric acid is preferably used.

[0098] As the conductivity salt, ammonium chloride, ammonium sulfate, ammonium sulfonate, and the like can be used, and among these, ammonium chloride is preferably used.

[0099] When a strongly acidic trivalent plating bath is used as the plating bath, the acidity is preferably weaker than pH 0.1, for example, a strongly acidic range of pH 0.1 to pH 0.6, and more preferably a strongly acidic range of pH 0.2 to pH 0.5.

[0100] When the pH is strongly acidic below pH 0.1, the electroplated film mainly composed of chromium using a trivalent chromium bath, which is the purpose of this embodiment, cannot be obtained. When the pH is higher than pH 0.6, the glossiness of the electroplated film deteriorates, and the absorption of impurity elements during the precipitation of chromium changes due to the film formation rate. Therefore, the electroplated film mainly composed of chromium, which is the purpose of this embodiment, cannot be obtained.

[0101] When a weakly acidic trivalent chromium bath is used as the electroplating bath, blue chromium (trade name of Atotech) can be used as an example of a commercially available product. When blue chromium is used, as an example, a pH range of 5.2 to 5.8 can be selected. The pH value is more preferably in the range of 5.4 to 5.6.

[0102] When the current density during electroplating is high, the film forming speed is fast and the productivity is high. In order to achieve the above composition, the current density can be adjusted from 45 to 100 A / dm 2 Under the conditions of high current density and high concentration of trivalent chromium salt, the film forming speed is fast, but the size of the film forming speed causes the availability of impurity elements during chromium precipitation to change. In order to obtain the above-mentioned desired chromium content and carbon content in the obtained electroplated film, it is desirable to have a preferred film forming speed.

[0103] It should be noted that the plating bath temperature is preferably high, and for example, can be selected within the range of 55° C. to 80° C.

[0104] The plating bath is preferably stirred by a slow stirring method such as flowing the plating solution near the surface to be plated. As the anode material, Pt, Ti, Ir, graphite, etc., which are highly insoluble, can be used.

[0105] The chromium electroplated film formed by the electroplating treatment has an amorphous structure when formed. The electroplated film with the amorphous structure is preferably subjected to heat treatment at a heating temperature of 250° C. to 400° C. to obtain an electroplated film with a crystallinity of 5% or more.

[0106] The degree of crystallinity is a value calculated from the peak integrated intensity ratio of the values ​​measured by X-ray diffraction measurement and the following formula (1).

[0107] Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1)

[0108] The integrated intensity ratio in formula (1) is a value obtained in XRD (X-ray diffraction) analysis based on 2θ: 30 to 60°, half-value width of crystalline: <3, and half-value width of amorphous: ≥3.

[0109] The heat treatment is performed to make the crystallinity of the electroplated film 5% or more. The heat treatment time is about 1.5 hours to 4.0 hours, for example, preferably about 2 hours. If the heat treatment is performed at a temperature exceeding 400° C., the mechanical properties of the steel material constituting the piston rod 21 will change, so it is not preferred.

[0110] The degree of crystallinity is more preferably in the range of 5% to 95%.

[0111] The electroplated film of this embodiment is preferably less likely to produce grinding marks due to the brittle mode when subjected to grinding processing. Figure 6 Polishing marks produced when polishing is performed using the film polishing apparatus shown.

[0112] Figure 6 The film polishing device 40 shown has driving rollers 41 and 42, which are arranged close to each other so as to be freely rotatable around the horizontal axis by bringing parts of their circumferential surfaces close to each other, and a rod raw material 21A for a piston rod to be processed can be placed on the boundary between these close driving rollers 41 and 42.

[0113] When the rod material 21A is arranged on the boundary portion between the driving rollers 41 and 42 that are arranged closely, the supported rod material 21A can be rotated about the axis along with the rotation of the driving rollers 41 and 42 .

[0114] A back pressure roller 43 is horizontally arranged above the rod material 21A at the boundary between the driving rollers 41 and 42 so as to be rotatable in the circumferential direction. A polishing film 44 can be supplied to the bottom surface of the back pressure roller 43 from a film supply device (not shown).

[0115] The polishing film 44 is a strip-shaped film, and the polishing film 44 can be supplied to the bottom surface side of the back pressure roller 43 from a film supply device (not shown) provided on one side in a direction perpendicular to the central axis of the back pressure roller 43 as indicated by arrow a. In addition, the film 44 can be moved and wound to a film winding device (not shown) provided on the other side in a direction perpendicular to the central axis of the back pressure roller 43 as indicated by arrow b. The polishing film 44 is wound on the film supply device of a necessary length, and can be continuously supplied to the bottom surface side of the back pressure roller 43.

[0116] The back pressure roller 43 is supported to be rotatable while being maintained in a horizontal state by an up-down moving mechanism (not shown), but is supported so that its up-down position can be finely adjusted by the up-down moving mechanism. A pressure head 45 supported by an up-down front-back moving mechanism (not shown) is provided above the back pressure roller 43. The pressure head 45 can be lowered from slightly above the back pressure roller 43 as shown by arrow c, while pressing the back pressure roller 43 downward with a prescribed pressure. In addition, the pressure head 45 is supported so that it can move freely along the axial direction of the back pressure roller 43 as shown by arrow d by the above-mentioned up-down front-back moving mechanism, and the pressure head 45 is supported so that it can move back and forth freely along the axial direction of the back pressure roller 43 while maintaining a state of pressing the back pressure roller 43 downward with a prescribed force.

[0117] Use three Figure 6The film polishing apparatus shown, for example, is loaded with a #600 polishing film in the first film polishing apparatus, a #400 polishing film in the second film polishing apparatus, and a #2000 polishing film in the third film polishing apparatus, and a piston rod polishing test is performed.

[0118] It should be noted that the grinding conditions are the same as the grinding conditions for sample 2 shown in FIG. 28 of International Publication No. 2021 / 193107. During grinding, the rotation speed of the driving rollers 41 and 42 is set to 1400 rpm, and the pressing force of the pressure head 45 is set to 0.15-0.3 MPa. The steel rod used in the test has a diameter of 22 mm and a length of 200 mm.

[0119] When the above-mentioned grinding process is performed, as an example, for example, the following examples and comparative examples are generated. Fig.11 The samples with grinding marks in the brittle mode shown in (A) and (B) or the samples with grinding marks in the brittle mode shown in (A) and (B) Fig.12 (A) and (B) are samples with grinding marks in the ductile mode.

[0120] Fig.11 The grinding marks shown in (A) and (B) are as follows Fig.11 The enlarged photograph of (B) clearly shows a sample having a polishing mark in a brittle mode indicating a peeling mark caused by brittle fracture.

[0121] Fig.12 The grinding marks shown in (A) and (B) are as follows Fig.12 The enlarged photograph of (B) shows a sample having polishing marks in a ductile mode without peeling marks.

[0122] In the production Fig.11 The electroplated coating with grinding marks shown in (A) and (B) is used for Figure 1~Figure 4 When the piston rod 21 is electroplated, Figure 5 In the step S8 shown, grinding marks of a brittle mode indicating peeling marks are generated on the surface by outer diameter grinding, and the surface cannot be finished to a desired surface roughness.

[0123] Figure 6 The film grinding device 40 shown is a device for finishing the outer peripheral surface of the piston rod, and is an important grinding device for finishing the outer peripheral surface of the piston rod to a desired surface roughness. During the outer diameter grinding, if the grinding marks of the above-mentioned brittle mode are generated, it will have a negative impact on the finishing accuracy of the outer peripheral surface of the piston rod, and excellent sliding characteristics, wear resistance and corrosion resistance cannot be obtained.

[0124] Therefore, as the electroplated film provided on the piston rod 21 applicable in the present embodiment, in the sample subjected to the above-mentioned grinding test, the grinding marks on the surface are observed, for example, by a microscope at a magnification of 200 times. Moreover, it is preferred to measure the number and width of the grinding marks in the same field of view, measure the number of grinding marks with a width of 8 μm or more, evaluate the quality of the electroplated film based on the number of generated grinding marks, and apply the selected electroplated film on this basis.

[0125] The reason why the grinding marks with a width of 8 μm or more were used as the criterion is that in the examples described below, when grinding tests were performed on a plurality of samples, the grinding marks in the brittle mode that produced peeling marks were mainly 8 μm or more in width.

[0126] According to the results of the embodiments described below, it is preferred to use a chromium electroplating film that contains, in addition to chromium, one or more impurity elements selected from carbon and oxygen, and contains chromium: 60 or more, carbon: 1at%~30at%, and after heat treatment, the indentation hardness of the outer surface is more than 11.1GPa, and the degree of crystallinity is more than 5%.

[0127] The chromium electroplating film can be obtained by using an electroplating bath containing the trivalent chromium salt, carboxylate, pH buffer and conductivity salt at pH 0.1 to 0.6, bath temperature 55°C to 80°C, cathode current density 45A / dm 2 ~100A / dm 2 It is obtained by electroplating under conditions of.

[0128] Under the above conditions, the electroplated film formed on the outer peripheral surface of the piston rod 21 and subjected to heat treatment has a film hardness of 11.1 GPa or more and a crystallinity of 5% or more. When the electroplated film has a film hardness of 11.1 GPa or more and a crystallinity of 5% or more, even when using Figure 6 Even when the film polishing apparatus 40 shown above performs outer diameter polishing under the above-mentioned conditions, peeling marks (fracture marks in the brittle mode) are unlikely to be generated.

[0129] Therefore, even if the above-mentioned grinding process is performed, the piston rod 21 without peeling marks can be obtained.

[0130] However, in the aforementioned embodiment, the electroplated component in which the electroplated coating of chromium using a trivalent chromium bath is formed relative to the piston rod (sliding contact component) 21 is described, but the electroplated coating can be applied to automobile parts such as piston rings and brake pistons, and can also be applied to the sliding surfaces of various sliding contact components such as shafts of hydraulic machines and gravure rollers of printing machines.

[0131] Example

[0132] A number of steel bars (22 mm in diameter, 200 mm in length) made of low carbon steel were prepared as test materials, and a trivalent chromium plating bath containing chromium chloride, glycine, boric acid, and ammonium chloride was used. The bath temperature was 65 to 75°C, and the current density was 45 to 100 A / dm 2 The electroplating treatment was carried out under the conditions of pH: 0.3~0.46, and a trivalent chromium electroplating film with a thickness of about 20μm was formed on the surface of the test material.

[0133] Figure 7 The results are shown in which the crystallinity (%) of each electroplated film was calculated based on the above formula (1) when the electroplated film was formed on each test material at 5 different film forming speeds while adjusting the current density. At any film forming speed, only halo patterns were observed in the XRD (X-ray diffraction) analysis results in the range of 2θ: 30 to 60°, so the electroplated film that remained in the film-forming state was an amorphous film with a crystallinity of 0.0%.

[0134] Figure 8 The component analysis results of each electroplated film formed at five film-forming speeds are shown. The component analysis was performed using an electron probe microanalyzer under the conditions of an accelerating voltage of 10 kV and an irradiation current of 100 nA.

[0135] like Figure 8 As shown, it can be confirmed that the chromium electroplated films formed using a trivalent chromium bath at various film formation rates contain trace amounts of chlorine and iron as impurity elements in addition to carbon and oxygen.

[0136] Among these impurity elements, carbon, which has the highest content, contains about 7at% to 23at%, and oxygen, which has the second highest content, contains about 3at% to 5at%. Other elements, such as chlorine and iron, contain trace amounts close to the detection limit.

[0137] according to Figure 8 It can be seen that the carbon content can be adjusted by adjusting the film forming speed of the electroplated film. It should be noted that the film forming speed can be selected to be more than 2.0 μm / min, and can be adjusted according to the amount of chromium chloride added to the chromium electroplating bath. Therefore, it can be recognized that the carbon content can be adjusted within the range of 5at% to 30at% by adjusting the electroplating conditions.

[0138] Three types of plated films were selected from the plurality of plated films. The indentation hardness of the plated films was measured for these samples. The components of the samples subjected to the hardness measurement were analyzed and the crystallinity was calculated. The results are shown in FIG. Fig. 9 However, the indentation hardness indicates the value of the instrumented indentation hardness measurement based on the nanoindentation method (ISO14577). The indentation weight used is 20 mN.

[0139] Fig. 9 The electroplated films of the test samples 1 to 3 shown have an indentation hardness of 8.5 GPa to 9.0 GPa, a crystallinity of 0% (amorphous), a chromium content of 76% to 88%, and a carbon content of 8% to 16%.

[0140] Fig. 9 When the samples 1 to 3 shown in the figure were subjected to the grinding test described below, it was determined that the grinding marks were in the brittle mode. Fig. 9 In the grinding mark mode column, the brittle mode is recorded. In addition, the pH of the plating solution used for the preparation of the test material is as follows: Fig. 9 shown.

[0141] For samples 1 to 3, the indentation hardness was measured after heat treatment at 200°C, 250°C, and 300°C for 2 hours, the crystallinity was calculated, and the film composition was analyzed. Fig.10 shown.

[0142] "Grinding Test"

[0143] Four grinding tests were conducted using Figure 6 In the film polishing apparatus shown, the first film polishing apparatus is loaded with a polishing film of #600, the second film polishing apparatus is loaded with a polishing film of #400, and the third film polishing apparatus is loaded with a polishing film of #2000.

[0144] It should be noted that the grinding conditions are the same as those for the sample 2 shown in FIG. 28 of International Publication No. 2021 / 193107. During grinding, the rotation speed of the driving rollers 41 and 42 is set to 1400 rpm, and the pressing force of the pressure head 45 is set to 0.15 MPa to 0.3 MPa.

[0145] Among the samples subjected to the grinding test, for the sample of Comparative Example 1-1 which was heat-treated at 200°C for 2 hours with respect to the sample 1, an image of the surface of the piston rod was taken by a scanning electron microscope at a magnification of 500 times, as shown in FIG. Fig.11 (A) shows an image taken at 5000 times magnification. Fig.11 (B) It can be confirmed that Fig.11 The vertical stripes in the up-and-down direction show the traces of polishing made by moving the polishing film along the direction of the vertical stripes.

[0146] like Fig.11 (B) shows an enlarged view of a polishing mark (peeling mark) that is believed to be a peeling failure caused by brittle fracture, which is generated along the moving direction of the polishing film. This polishing mark can be recorded as a polishing mark of a brittle mode.

[0147] In addition, for the sample 1, regarding the sample of Example 1-3 which was heat treated at 300°C for 2 hours, the surface of the piston rod was magnified 500 times using a scanning electron microscope and the following image was taken: Fig.12 (A) shows an image taken at 5000 times magnification. Fig.12 (B) shown.

[0148] like Fig.12 (B) shows an enlarged view of a polishing mark in a flow shape along the moving direction of the polishing film due to shear deformation. This polishing mark can be recorded as a polishing mark in a ductile mode.

[0149] Fig.13 (A) shows the analysis results of X-ray diffraction of the sample 3 (amorphous electroplated film). Fig.13 (B) is a surface photograph showing the polishing marks of the sample at 200 times magnification. Fig.13 In the surface photograph shown in (B), three polishing marks (accompanied by peeling failure) with a width of 8 μm or more can be confirmed as indicated in front of the arrows.

[0150] Fig.14 This is a graph showing the results of X-ray diffraction analysis of Example 3-4 in which a heat treatment (baking treatment) at 250° C. for 2 hours was performed on the sample of Sample 3. Fig.14 From the analysis results of X-ray diffraction shown, it can be determined that the sample of Example 3-5 in which the sample 3 was heat-treated at 250° C. is a sample with a sharp peak and a high degree of crystallinity.

[0151] Fig.15 (A) shows the analysis results of X-ray diffraction of the sample of the test material 3 subjected to a heat treatment (baking treatment) at 300° C. for 2 hours. Fig.15 (B) is a surface photograph showing the polishing marks of the sample.

[0152] according to Fig.13 The X-ray diffraction analysis results shown in (A) show that the sample 3 is a 100% amorphous sample (crystallization degree 0.0%) showing only halo lines. Fig.15 The X-ray diffraction analysis results shown in (A) show that the sample of Example 3-5 in which the sample 3 was heat-treated at 300° C. was determined to be a crystalline sample having a sharp peak.

[0153] Fig.13 The amorphous electroplated film shown in (B) has three grinding marks with a width of more than 8 μm. Fig.15 The crystalline plated film shown in (B) has no polishing marks with a width of 8 μm or more.

[0154] According to the above formula (1), the degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100%. The integrated intensity ratio of formula (1) is calculated by Fig.13 In (A), 2θ: 30°~60°, half-value width of crystalline: <3, half-value width of amorphous: ≥3.

[0155] according to Fig.13 According to the analysis results of X-ray diffraction shown in (A), the degree of crystallinity calculated based on formula (1) was 0%.

[0156] according to Fig.14 The X-ray diffraction analysis results shown in (A) show that the degree of crystallinity calculated based on formula (1) is 13.2%. Fig.15 According to the analysis results of X-ray diffraction shown in (A), the degree of crystallinity calculated based on formula (1) was 12%.

[0157] Therefore, a crystalline electroplated film having a crystallinity of 5% or more, for example Fig.10 The plating films with a thickness of 7% to 44% shown above are less likely to produce polishing marks in the problematic brittle mode.

[0158] For including Fig.10 For each sample shown, a plurality of piston rods were produced using the same grinding conditions as those for these samples, and the number and width of friction marks present within a field of view at 200 times magnification were observed at three locations using a metal microscope.

[0159] As a result, in both the sample without heat treatment and the sample after heat treatment at 200°C, multiple polishing marks with a width of 8 μm or more were confirmed, and peeling failure was confirmed in the polishing marks with a width of 8 μm or more. Fig.10 In the samples of the examples shown, no polishing marks resulting from peeling were observed.

[0160] Based on the above results, when the plated film is subjected to the above polishing test, the number of polishing marks with a width of 8 μm or more is counted, which is used as a criterion for determining whether the plated film is in a brittle mode or a ductile mode in the above polishing test.

[0161] Fig.16 This is a graph showing the relationship between the maximum polishing mark width generated by the heat treatment temperature (represented as baking temperature in the figure) and the above-mentioned polishing test in the electroplated film formed at each deposition rate (film formation rate).

[0162] In the sample where the heat treatment temperature was set to 200°C, a plurality of polishing marks with a width of 8 μm or more were generated. However, when the heat treatment temperature was set to 250°C or 300°C, no polishing marks with a width of 8 μm or more were generated.

[0163] Fig.17 This is a graph showing the relationship between the heat treatment temperature (baking temperature) and the number of polishing marks with a width of 8 μm or more generated by the above-mentioned polishing test in the plated film formed at each deposition rate (film formation rate).

[0164] In the sample where the heat treatment temperature was set to 200°C, many polishing marks with a width of 8 μm or more were generated. However, when the heat treatment temperature was set to 250°C or 300°C, no polishing marks with a width of 8 μm or more were generated.

[0165] Fig.18 This is a graph showing the relationship between the heat treatment temperature (baking temperature) and the film hardness in the electroplated films formed at various film formation rates (precipitation rates).

[0166] Some of the samples without heat treatment and the samples with heat treatment temperature set to 200°C had hardness less than 11.1 GPa. However, when the heat treatment temperature was set to 250°C or 300°C, the hardness of the plated film exceeded 11.1 GPa.

[0167] Fig.19 This is a graph showing the relationship between the heat treatment temperature (baking temperature) and the degree of crystallization in the plated films formed at various film formation rates.

[0168] When the heat treatment temperature exceeds 200° C., crystallization proceeds, and when the heat treatment temperature exceeds 250° C., the degree of crystallization increases, resulting in a plated film having a degree of crystallization of 5% or more.

[0169] Fig. 20 The graph shows the results of measuring the hardness (GPa) of the plated film and the number of polishing marks (lines / mm) with a width of 8 μm or more for the plated films formed at each (deposition speed) film formation rate.

[0170] Fig.21 The results of measuring the crystallinity (%) of the plated film and the number of polishing marks (lines / mm) with a width of 8 μm or more for the samples of the examples and the comparative examples are shown.

[0171] Fig. 22 Indicates based on Fig. 20 , Fig.21 The results shown are the correlation between the hardness of the plated film and the degree of crystallinity of the plated film.

[0172] like Fig.21 As shown, the number of brittle mode grinding marks varies greatly with a crystallinity of 5%. When the crystallinity is less than 1%, the number of brittle mode grinding marks varies depending on the sample, but when the crystallinity is above 5%, the frequency of occurrence is low in any sample.

[0173] like Fig. 22 As shown, the hardness of the plated film is around 11.1 GPa, and the crystallinity of the samples having a higher surface indentation hardness than that of the plated film is 5% or more.

[0174] When the surface indentation hardness is 10.3 GPa or more, the number of polishing marks with a width of 8 μm or more can be suppressed, so it is preferred. When it is 10.9 GPa or more, the frequency of occurrence is smaller and it is preferred. As for the heat treatment temperature, in the samples above 250° C., in any sample, it is a value exceeding 11 GPa (11.1 GPa or more), which is appropriate.

[0175] Based on these results, it is considered that the physical properties of the coating are caused by organic components such as carboxylates, pH buffers, and conductive salts in the electroplating bath. In addition, the amount of organic components contained in the coating also changes depending on the pH, bath temperature, and current density conditions during electroplating. Furthermore, by performing heat treatment to form an electroplated coating with a crystallinity of more than 5%, even if a finishing treatment such as grinding is performed, it can become an electroplated coating that does not produce peeling marks.

[0176] Industrial Applicability

[0177] According to the above-mentioned aspect of the present invention, it is possible to provide an electroplated component having an electroplated coating mainly composed of chromium using a trivalent chromium bath which is less environmentally friendly than hexavalent chromium and which is less susceptible to peeling and damage during grinding. In addition, it is possible to provide a manufacturing method for manufacturing the electroplated component. Therefore, the industrial applicability is large.

[0178] Description of Reference Numerals

[0179] 1…Shock absorber (cylinder device)

[0180] 2…Inner tube (cylinder)

[0181] 3…outer cylinder

[0182] 15…Oil seal

[0183] 21…Piston rod (sliding contact part)

[0184] 25…Piston

[0185] A…Sliding range

Claims

1. A plated component having, on its outer surface, a plated film containing at least chromium, carbon and oxygen and having chromium as a main component using a trivalent chromium bath, The electroplated film contains chromium: 60 at% or more, carbon: 1 at% to 30 at%, and the indentation hardness of the outer surface is 11.1 GPa or more. The peak integrated intensity ratio of the measured value of the X-ray diffraction measurement and the crystallinity calculated by the following formula (1) is 5% or more, Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1) in, The indentation hardness is a value measured by instrumented indentation hardness using a nanoindentation method (ISO14577), and the integrated intensity ratio of formula (1) is a value obtained in XRD (X-ray diffraction) analysis with 2θ: 30° to 60°, half-value width of crystalline: <3, and half-value width of amorphous: ≥3.

2. The electroplated component according to claim 1, The plated part is a sliding contact part that is slidably contacted by the sliding part.

3. The electroplated component according to claim 1 or claim 2, The oxygen concentration of the electroplated film is 2 at% to 6 at%.

4. A method for manufacturing an electroplated component, wherein the electroplated component has an electroplated film on its outer surface that contains at least chromium, carbon, and oxygen and has chromium as a main component using a trivalent chromium bath, The electroplated film contains chromium: 60 at% or more, carbon: 1 at% to 30 at%, and the indentation hardness of the outer surface is 11.1 GPa or more. In the above-mentioned electroplated film, the peak integrated intensity ratio of the measured value of the X-ray diffraction measurement and the crystallinity calculated by the following formula (1) are 5% or more, The method for manufacturing the electroplated component comprises an electroplating process for forming an electroplated film composed of a hard layer with chromium as a main component on the surface of the electroplated component, wherein the electroplating process comprises a first step of forming an amorphous electroplated film; a second step of heating and crystallizing the amorphous electroplated film formed in the first step; Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1) in, The indentation hardness is a value measured by instrumented indentation hardness using a nanoindentation method (ISO14577), and the integrated intensity ratio of formula (1) is a value obtained in XRD (X-ray diffraction) analysis with 2θ: 30° to 60°, half-value width of crystalline: <3, and half-value width of amorphous: ≥3.

5. The method for manufacturing a plated component according to claim 4, In the electroplating process, in an electroplating bath containing a trivalent chromium salt, a carboxylate, a pH buffer material and a conductivity salt, the bath temperature is 55°C to 80°C, and the cathode current density is 45A / dm 2 ~100A / dm 2 The electroplating film is formed under the conditions of.

6. The method for manufacturing a plated component according to claim 4 or claim 5, The plated part is a sliding contact part that is in sliding contact with the sliding part.

7. The method for manufacturing a plated component according to claim 4 or claim 5, The oxygen concentration of the electroplated film is 2 at% to 6 at%.

8. The method for manufacturing a plated component according to claim 4 or claim 5, The heating temperature in the second step is 250°C to 400°C.

Citation Information

Patent Citations

  • Gravure plate making roll and its manufacturing method

    JP2008143169A